Coexistence of ulcerative colitis and Sjögren's syndrome in a patient with Takayasu's arteritis and Hashimoto's thyroiditis - Hyun Woo Park; Hyun Seok Lee; Sejin Hwang; Han Sol Lee; Han-Ik Bae; Ghilsuk Yoon (Intestinal Research, 2017)
A 31-year-old woman with a 15-year history of Takayasu's arteritis (TA) and a 13-year history of Hashimoto's thyroiditis presented with hematochezia. She received a diagnosis of Sjögren's syndrome at 1 month before her visit to Kyungpook National University Medical Center. Her colonoscopic findings were compatible with a diagnosis of ulcerative colitis (UC). She was treated with oral mesalazine, and her hematochezia symptoms subsequently disappeared. The coexistence of UC and TA has been reported; however, reports on the coexistence of UC and Sjögren's syndrome, or of UC and Hashimoto's thyroiditis are rare. Although the precise etiologies of these diseases are unknown, their presence together suggests that they may have a common pathophysiologic background. Furthermore, in patients with autoimmune or vascular diseases, including TA, systemic manifestations should be assessed with consideration of inflammatory bowel diseases including UC in the presence of gastrointestinal symptoms such as diarrhea and hematochezia.